A DICOM ENCRYPTION ALGORITHM TO INCREASE SECURITY AND PRIVACY IN HEALTH DATA MANAGEMENT BASED ON PATIENT BIOMETRICS DATA, ARTIFICIAL INTELLIGENCE, AND RNA ENCRYPTION ALGORITHM - Soltani, Mohammad; Shakeri, Hassan; Houshmand, Mahboobeh (Eurasian Journal of Mathematical and Computer Applications, 2025)
In the modern era, unauthorized access to health information systems (HIS) and electronic health records (EHR) must be prevented. In the subject of health data management (HDM), cyber-attacks are one of the important security risks. Medical information, such as EHR is delivered over an open network. Various approaches and technologies are used to ensure the security of medical information. One such technology is encryption, which protects medical images. This paper proposes an efficient hybrid encryption algorithm to secure digital imaging and communications (DICOM) in healthcare. The proposed algorithm uses artificial intelligence and RNA encryption. In the proposed algorithm, before receiving the patient’s DICOM image, the patient’s biometric information is evaluated using artificial intelligence, and if the received biometric is correct, in the next steps, DICOM is encrypted using an RNA encryption algorithm. The proposed encryption algorithm uses a patient’s biometric information such as iris or fingerprint to create keys. According to the results of the proposed algorithm, the maximum entropy is more than 7.9998, NPCR is about 99.899, UACI is about 33.43, key space is more than 1089, and correlation is Nonzero. This means that our algorithm is robust against brute-force attacks.